Apache Spark: A Unified Engine for Big Data Processing. - ZAHARIA, MATEI; XIN, REYNOLD S.; WENDELL, PATRICK; DAS, TATHAGATA; ARMBRUST, MICHAEL; DAVE, ANKUR; XIANGRUI MENG; ROSEN, JOSH; VENKATARAMAN, SHIVARAM; FRANKLIN, MICHAEL J.; GHODSI, ALI; GONZALEZ, JOSEPH; et al. (Communications of the ACM, 2016)
The article discusses the open source computing framework, Apache Spark, which unifies streaming, batch, and interactive big data workloads to unlock new applications. Topics include Spark's use of an RDD programming model, the use of Spark in diverse applications such as batch processing and image processing, and the additional cost of Spark over other specialized systems due to fault tolerance.